Technopreneurship as a Pathway to Sustainable Business Performance: Empirical Evidence from SMES in Nigeria: Array - Oyedele, Ola Olusegun; Ojeaga, Paul, I.; Ganiyu, Idris Olayiwola; Derera, Evelyn; Oyero, Mutiu Adeleke (The Journal of Accounting and Management, 2020)
The overall objective of the study was to examine empirical evidences on how technopreneurship impacts business sustainability carried out in some selected areas in Abeokuta, Nigeria. A sample of 126 respondents were selected using Yaro Yamane random sampling method. A primary method of data collection was used, a well-structured questionnaire was administered, and responses were analysed using linear regression. The frequency of responses to each of the explanatory variables in the questionnaire are shown using frequency tables. The study findings which were based on the test of two (2) hypotheses in the study, show that intellectual property rights have significant impact (R 2 = 0.294 and P = 0.000) on business profitability, research and development and innovation (R&D&I) has a direct positive (R 2 = 0.292 and P = 0.000) effect on business earned revenue. The study recommends that businesses should possess or sell and commercialise intellectual property rights (IPRs) and engage in research, development and innovation as this boosts business turnover or sales revenue earned. Finally, technopreneurship should be a central concern for government and policymakers.